Quantitative assessment of the oral microvasculature using optical coherence tomography angiography - Zhang, Tianyu; Zhang, Yilong; Liao, Jinpeng; Shepherd, Simon; Huang, Zhihong; Macluskey, Michaelina; Li, Chunhui (Frontiers in Bioengineering and Biotechnology, 2024)
Early diagnosis of oral squamous cell carcinoma can greatly improve treatment success rate and patient survival. Although Optical Coherence Tomography (OCT) based Angiography (OCTA) is a promising in vivo technique in oral imaging, there is a need for objective assessment of oral microvasculature. This study aimed to demonstrate a comprehensive methodology of quantitative assessing OCTA intraoral scanning results to provide measurable, reproducible data and to avoid subjective visual interpretations. Data were collected from 37 healthy subjects in total across four intraoral sites—buccal mucosa (n=32), labial mucosa (n=24), floor of the mouth (n=13), and hard palate (n=8)—using a non-invasive swept-source OCT system. Four quantitative metrics—vessel area density, vessel skeleton density, vessel diameter index, and a newly proposed weighted Tortuosity Index—were used to assess OCTA images in oral applications. The quadruple quantitative assessment's repeatability was evaluated to be reliable. Analysis of a benign ulcer case revealed differences in these metrics compared to healthy cases. In conclusion, we demonstrated a comprehensive method to quantify microvasculature in the oral cavity, showing considerable promise for early diagnosis and clinical management of oral diseases.